1994
DOI: 10.1136/bjo.78.8.612
|View full text |Cite
|
Sign up to set email alerts
|

Refractive outcome following diode laser versus cryotherapy for eyes with retinopathy of prematurity.

Abstract: The refractive error in 15 eyes with threshold retinopathy of prematurity treated with diode laser photocoagulation was compared with 25 eyes with the same disease severity treated by cryotherapy. Myopia was present in 40% (six eyes) of the first group ranging from -1*50 to -3*50 dioptres, while 92% (23 eyes) showed myopia which ranged from -050 to -8-00 dioptres in the cryotherapy group. Sixty per cent (nine eyes) were hypermetropic at less than +3.0 dioptres in the laser group, while only 8% (two eyes) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 19 publications
3
49
1
1
Order By: Relevance
“…3,4,6 The reported rates of myopia and high myopia were even higher in patients treated with cryotherapy, ranging from 82.9 to 92.0% and 32.0 to 52.5%, respectively (Table 3). [5][6][7] In the current study, the percentages of patients with myopia and high myopia among IVB-treated patients were 47.5 and 10.0%, respectively, which are less than the previously reported percentages for patients treated with laser treatment or cryotherapy. …”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…3,4,6 The reported rates of myopia and high myopia were even higher in patients treated with cryotherapy, ranging from 82.9 to 92.0% and 32.0 to 52.5%, respectively (Table 3). [5][6][7] In the current study, the percentages of patients with myopia and high myopia among IVB-treated patients were 47.5 and 10.0%, respectively, which are less than the previously reported percentages for patients treated with laser treatment or cryotherapy. …”
Section: Discussioncontrasting
confidence: 48%
“…2 However, many investigators have reported high prevalences of myopia and high myopia in preschool-and school-age children who received ablative therapy. [3][4][5][6][7] For these patients, it has been reported that laser treatment for severe ROP results in less myopia than cryotherapy. 6 In the last several years, anti-vascular endothelial growth factor (VEGF) agents have emerged as a new treatment for ROP, and promising experiences have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] There have been reports that cryotherapy in threshold ROP contributes to the development of myopia and that laser photocoagulation, in comparison, produces less myopic shift. [5][6][7] However, Quinn et al felt that the cryotherapy did not result in additional myopia but that the high myopia was related to the cicatricial retinopathy or severity of ROP. 8 In recent times, laser photocoagulation has largely replaced cryotherapy as the established treatment modality for ROP.…”
mentioning
confidence: 99%
“…In these cases there is also evidence of alterations in the development of the anterior segment: microcornea, corneal curvature and lens increase 16,19 . The fact that preterm children with retinopathy present a greater disposition to myopia-like refractive errors [3][4][5][6][7][8] was again confirmed in this study and, considering the degree of myopia according to the performed treatment, we deem that the risk for severe myopia is higher in those patients who received cryotherapy than in those treated with lasertherapy, similarly to the data found in the world literature 6,15,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In these cases there is also evidence of alterations in the development of the anterior segment: microcornea, corneal curvature and lens increase 16,19 . The fact that preterm children with retinopathy present a greater disposition to myopia-like refractive errors 3-8 was again confirmed in this study and, considering the degree of myopia according to the performed treatment, we deem that the risk for severe myopia is higher in those patients who received cryotherapy than in those treated with lasertherapy, similarly to the data found in the world literature 6,15,19 .There are still controversial conclusions regarding the visual prognosis of the patients with retinopathy of prematurity treated with lasertherapy or cryotherapy 6,15 . Some studies showed that visual results are better in patients treated with laser 7,15 and a hypothesis for these results would be induction of lower myopia degrees.…”
mentioning
confidence: 99%